Human Herpesvirus-8 Infection Associated with Kaposi Sarcoma, Multicentric Castleman's Disease, and Plasmablastic Microlymphoma in a Man with AIDS: A Case Report with Review of Pathophysiologic Processes. (30th December 2010) - Eaton, Christian; Dorer, Russell; Aboulafia, David M.
Abstract : Kaposi sarcoma (KS), multicentric Castleman's disease (MCD), and plasmablastic microlymphoma, are all linked to human herpesvirus-8 (HHV-8) infection and HIV-induced immunodeficiency. Herein, we describe the case of a Kenyan man diagnosed with HIV in 2000. He deferred highly active antiretroviral therapy (HAART) and remained in good health until his CD4+ count declined in 2006. He was hospitalized with bacterial pneumonia in 2008, after which he agreed to take HAART but did so sporadically. In 2010, he was hospitalized with fever, lymphadenopathy, pancytopenia, and an elevated HHV-8 viral load. A lymph node biopsy showed findings consistent with KS, MCD, and plasmablastic microlymphoma. Eight months after starting liposomal doxorubicin, Rituximab, and a new HAART regimen, he has improved clinically, and his HIV and HHV-8 viral loads are suppressed. These three conditions, found in the same lymph node, underscore the inflammatory and malignant potential of HHV-8, particularly in the milieu of HIV-induced immunodeficiency.